How is a specialist depression service effective for persistent moderate to severe depressive disorder?: a qualitative study of service user experience - Thomson, Louise; Barker, Marcus; Kaylor-Hughes, Catherine; Garland, Anne; Ramana, Rajini; Morriss, Richard; Hammond, Emily; Hopkins, Gail; Simpson, Sandra (BioMed Central, 2018)
Background. A specialist depression service (SDS) offering collaborative pharmacological and cognitive behaviour therapy treatment for persistent depressive disorder showed effectiveness against depression symptoms versus usual community based multidisciplinary care in a randomised controlled trial (RCT) in specialist mental health services in England. However, there is uncertainty concerning how specialist depression services effect such change. The current study aimed to evaluate the factors which may explain the greater effectiveness of SDS compared to Treatment as Usual (TAU) by exploring the experience of the RCT participants . Methods. Qualitative audiotaped and transcribed semi-structured interviews were conducted 12-18 months after baseline with 21 service users (12 SDS, 9 TAU arms) drawn from all three sites. Inductive thematic analysis using a grounded approach contrasted the experiences of SDS with TAU participants. Results. Four themes emerged in relation to service user experience: 1. Specific treatment components of the SDS: which included sub-themes of the management of medication change, explaining and developing treatment strategies, setting realistic expectations, and person-centred and holistic approach; 2. Individual qualities of SDS clinicians; 3. Collaborative team context in SDS: which included sub-themes of communication between healthcare professionals, and continuity of team members; 4. Accessibility to SDS: which included sub-themes of flexibility of locations, frequent consultation as reinforcement, gradual pace of treatment, and challenges of returning to usual care. Conclusions. The study uncovered important mechanisms and contextual factors in the SDS that service users experience as different from TAU, and which may explain the greater effectiveness of the SDS: the technical expertise of the healthcare professionals, personal qualities of clinicians, teamwork, gradual pace of care, accessibility and managing service transitions. Usual care in other specialist mental health services may share many of the features from the SDS. Trial Registration: “Trial of the Clinical and Cost Effectiveness of a Specialist Expert Mood Disorder Team for Refractory Unipolar Depressive Disorder” was registered in www.ClinicalTrials.gov (NCT01047124) on 12-01-2010 and the ISRCTN registry (ISRCTN10963342) on 25-11-2015 (retrospectively registered).